الحقل المدرسي وإعادة إنتاج مواضيع غير ظاهرة وأخرى واقعية - وشنان, حكيمة (Changement Social; No 06 (2019): revue change social, 2019)
للمدرسة حرمتها و قدسيتها في كل المجتمعات بنية ووظيفة، لكن قد يحدث و تتعرض لممارسات و ظواهر تخدش هذه القدسية و الحرمة، ما يتطلب البحث بشأنها و ما تعيشه من ظواهر، مثل ذلك مسألة العنف كظاهرة معطاة للعيان، اتخذت لنفسها مكانا في كافة المؤسسات التعليمية، و لو بدرجات متفاوتة، حتى باتت تغزو البعض منها أكثر من غيرها. ما دفع الباحثين على اختلاف تخصصاتهم العلمية للإنكباب عليها ودراستها، من مختلف الزوايا، فمرة باعتبارها نتاج صراع علائقي و تفاعلي بين الفاعلين التربويين، تحدث نتيجة الشعور بالألم و التهميش وحتى الإقصاء و الأذى ما يدفع للتمرد على المؤسسة ومن فيها وعدم الخضوع لقواعدها التي يتصور أنه لا يستفاد منها شيئا، ومرة باعتبارها نتاج عدة عوامل متداخلة أسرية، نفسية، اجتماعية وحتى اقتصادية وسياسية. ورغم أن هذه الظاهرة كانت دائما موجودة لكن ما تغير هو كيفية النظر إليها، حتى باتت من المواضيع الواقعية المفروضة في مرحلة زمنية معينة، مثل الشباب المخدرات، الفساد، الإرهاب، التكنولوجيا. ليتم بذلك استبعاد بعض المواضيع غير الظاهرة رغم تحريكها للعنف في المدارس، مثل التمييز الإقصاء، المحاباة، الجهوية، لأن المدرسة ظلت تنتجها ولا تزال تعيد إنتاجها. من أجل ذلك، تأتي هذه الورقة، للتقصي بشأن الموضوع المطروح، تقصيا يأخذ بالتوضيح  النظري والتمثل الواقعي. وكل ذلك في ظل استلاف مفاهيم "بورديو" لكن بوجهة نظر مغايرة كلما تطلب الأمر ذلك. school has it’s holiness and sanctity in both structure and function in all societies. But, it happens to be subjected to exertions and phenomena that affect its holiness and sanctity. Which requires search about it within the phenomenon? As an example the matter of violence getting progressively wide in quite different levels in all educational establishments till it dominated almost of them. This urged researchers in different scientific majoring to put a spot light on and study it from different angles. Sometimes, considering it as a results of relational and reactive conflict between educative actors. Furthermore, feeling hurted, marginalize and even excluded. They rebel against the establishment, the staff and the rules feeling no benefits from it. Moreover, many other familial, psychological, social, economical and political factors contributed to this phenomenon. Although it did exist before, but what has been changing is the vision at it till became the real imposed subject in a specific period of time like youth, drugs, fraud, terrorism, and technology. This led to keeping out some hidden subjects though it manages violence such as racism excluding nepotism and regionalism because school still producing and reproducing it.comes to retrace in the given subject, retrace that takes theoretical clarification and real exampling. All that for shadowing the conceptions of Pierre Bourdieu, but in different vision according to the requirement of the subject.